2015
DOI: 10.1088/1612-2011/12/8/085801
|View full text |Cite
|
Sign up to set email alerts
|

Impulsive stimulated Raman scattering in tetragonal GdVO4single crystal: many-phonon Stokes and cross-cascaded lasing

Abstract: For the first time we excited four-phonon impulsive stimulated Raman scattering (SRS) in tetragonal GdVO4 single crystal under near-IR femtosecond pumping. All of its recorded χ(3)-nonlinear Stokes cascaded and cross-cascaded fully coherent lasing emissions were identified at internal vibrations of the [VO4]3− units of the studied vanadate. The obtained new fundamental knowledge could significantly enrich the functional potential of this crystal, which is a host crystal for trivalent lanthanide lasants and att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…In χ (3) —non‐linear femtosecond coherent lasing, all the internal vibrations of vanadium complexes [VO 4 ] 3− of the studied crystals are observed. Some of them were not recorded earlier in steady‐state picosecond SRS‐experiments and in preliminary constant pulse shape femtosecond χ (3) ‐laser measurements .…”
Section: Impulsive Srs Lasingmentioning
confidence: 99%
See 1 more Smart Citation
“…In χ (3) —non‐linear femtosecond coherent lasing, all the internal vibrations of vanadium complexes [VO 4 ] 3− of the studied crystals are observed. Some of them were not recorded earlier in steady‐state picosecond SRS‐experiments and in preliminary constant pulse shape femtosecond χ (3) ‐laser measurements .…”
Section: Impulsive Srs Lasingmentioning
confidence: 99%
“…Unfortunately, in the study of the high-peak power Ln 3þ :REVO 4 lasers, careful attention is not always given to the SRS issue. Our recent preliminary research on impulsive SRS crystals m-LaVO 4 and t-GdVO 4 showed that the risk of unwanted impulsive self-SRS will be greater at high intra-cavity power [38,39]. Therefore, we report more complete data on the spectral composition of femtosecond ISRS lasing for two tetragonal t-YVO 4 and t-GdVO 4 and monoclinic m-LaVO 4 vanadates.…”
mentioning
confidence: 98%
“…Now, let us discuss briefly the vibronic nature of χ (3) active phonon modes of the m LaVO 4 and t GdVO 4 crystals, which are the vibrations of their structural vanadium complexes [VO 4 ] 3with nearly identical tetrahedral shape [11]. Monoclinic m LaVO 4 exhibits two types of Raman active oscilla tions, A g and B g [6], among which the ISRS lasing modes ω SRS1 ~855 cm -1 and ω SRS3 ~ 820 cm -1 can be the totally symmetric stretching A g (ν s ) of its vanadium complexes [VO 4 ] 3- [12] and the modes ω SRS2 3 70 cm -1 and ω SRS4 ~ 305 cm -1 can belong to the anti symmetric bending A g /B g (δ as ).…”
Section: Femtosecond Srs Generation Of Coherent Optical Phonons In Vamentioning
confidence: 99%
“…The ISRS generation of the monoclinic m LaVO 4 and tetragonal t GdVO 4 crystals was studied at room temperature on a femtosecond facility based on a ytterbium fiber laser excitation source with λ e 1 .0615 μm and ω e ~ 9421 cm -1 ) and a detecting dif fraction spectrometer with an InGaAs CMOS detec tor (G10768 1024D) [11]. The excitation pulse length was chosen to be ~600 fs, which ensured the impulsive SRS lasing of crystals with the detection of their mul tiphonon spectra with nonoverlapping generation lines.…”
mentioning
confidence: 99%
See 1 more Smart Citation